Treatment of cattle with DNA-encoded Flt3L and GM-CSF prior to immunization with Theileria parva candidate vaccine antigens induces CD4 and CD8 T cell IFN-γ responses but not CTL responses - Mwangi, David Miano; Honda, Y.; Graham, S.P.; Pelle, Roger; Taracha, E.L.N.; Gachanja, J.; Nyanjui, J.K.; Bray, J.; Palmer, G.H.; Brown, W.C.; Mwangi, W. (Elsevier, 2011)
Theileria parva antigens recognized by cytotoxic T lymphocytes (CTLs) are prime vaccine candidates against East Coast Fever in cattle. A strategy for enhancing induction of parasite-specific T cell responses by increasing recruitment and activation of dendritic cells (DCs) at the immunization site by administration of bovine Flt3L and GM-CSF prior to inoculation with DNA vaccine constructs and MVA boost was evaluated. Analysis of immune responses showed induction of significant T. parva-specific proliferation, and IFN-γ-secreting CD4+ and CD8+ T cell responses in immunized cattle. However, antigen-specific CTLs were not detected. Following lethal challenge, 5/12 immunized cattle survived by day 21, whereas all the negative controls had to be euthanized due to severe disease, indicating a protective effect of the vaccine (p < 0.05). The study demonstrated the potential of this technology to elicit significant MHC class II and class I restricted IFN-γ-secreting CD4+ and CD8+ T cells to defined vaccine candidate antigens in a natural host, but also underscores the need to improve strategies for eliciting protective CTL responses.